2019
DOI: 10.2174/1872211312666180723160624
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and In Vitro Growth Inhibition Study of Struvite Urinary Stones Using Oxalis corniculata Linn. Leaf Extract and its Biofabricated Silver Nanoparticles

Abstract: The present work confirms the inhibitory activity of the aqueous extract of edible O. corniculata and its biofabricated silver nanoparticles against urinary tract infection (UTI) causing bacteria and urolithiasis. Therefore, the consumption of O. corniculata in our daily diet may reduce the risk of UTI and urolithiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In their analysis, the results of agar well diffusion and microdilution tests were not consistent [63]. In a study by Das et al the antibacterial activity of O. corniculata aqueous extract as biofabricated silver nanoparticles (AgNPs) against UTI-causing bacteria was many times higher than normal extract [64]. Rahman et al found that methanolic extract had more bacteriostatic activity against Gram-positive and Gram-negative bacteria than ethanolic extract, but the bacteriostatic activity of both extracts was lower than that of the cephachlore antibiotic [65].…”
Section: Discussionmentioning
confidence: 95%
“…In their analysis, the results of agar well diffusion and microdilution tests were not consistent [63]. In a study by Das et al the antibacterial activity of O. corniculata aqueous extract as biofabricated silver nanoparticles (AgNPs) against UTI-causing bacteria was many times higher than normal extract [64]. Rahman et al found that methanolic extract had more bacteriostatic activity against Gram-positive and Gram-negative bacteria than ethanolic extract, but the bacteriostatic activity of both extracts was lower than that of the cephachlore antibiotic [65].…”
Section: Discussionmentioning
confidence: 95%
“…The EDAX analysis shows the elements outline as well as the amount of biosynthesized CuNPs Copper oxide nanoparticles are formed (Fig. 7) (Das et al, 2018).…”
Section: Edax Analysismentioning
confidence: 99%
“…Saleh et al [126] formulated and investigated the mechanisms of antimicrobial action of two different types of metallic NPs, i.e., Ag-based and titanium dioxide-based NPs, against Proteus vulgaris and Proteus mirabilis, reporting that both kinds of NPs inhibited the microbial species via downregulation of fliL gene expression directly associated with blockade of the movement of the Proteus species. Similarly, Das et al [127] created Ag NPs loaded with the extract of Oxalis corniculata and observed that compared with pure extract, extract-based Ag NPs exhibited significantly higher antimicrobial activities against both Gram-positive and Gram-negative bacterial strains, the leading cause of UTIs. In addition, the authors also reported that the formulations allowed for significantly higher kidney stone dissolution, an effect further increased in the presence of Ag NPs.…”
Section: Silver-based Npsmentioning
confidence: 99%